Pengaruh Penambahan Limbah Plastik Pada Refused Derived Fuel Terhadap Fuel Conversion Rate Pada Dual Reactor Fluidized Bed - Riadi, Selamet; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya (Teknik Desain Mekanika, 2022)
Abstract Plastic is often a problem experienced by several countries around the world including Indonesia. One of the places that attracts foreign tourists in Indonesia is Bali Island. Along with the growth of tourism on the island of Bali, the amount of plastic waste generated continues to increase. One technology that can convert plastic waste into energy is gasification technology. This gasification technology can convert waste into energy by converting fuel into gas with a combustion process and limited air supply The purpose of this study was to determine the effect of the addition of plastic waste to the Fuel Conversion Rate in Dual Reactor Fluidized Bed fueled by Refused Derived Fuel with the addition of 1%, 2%, and 3% plastic from 0.6 kg of organic waste. The difference in the amount of plastic mixture will produce different fuel characteristics so that the best fuel mixture can be known. The results showed that in the variation with the addition of 1% plastic mass, the result was a Fuel Conversion Rate of 0.186 kg/hour, an additional 2% of plastic mass, a Fuel Conversion Rate of 0.1 kg/hour was obtained, and with the addition of 3 % of plastic mass, the result is a Fuel Conversion Rate of 0.028 kg/hour. Keywords: Gasification, Fuel Conversion Rate, addition of 1%, 2%.and 3% plastic mass